Factors Affecting Social Support Status of People Living with HIV/AIDS at Selected Hospitals of North Shewa Zone, Amhara Region, Ethiopia. (5th April 2021) - Basha, Elyas Admasu; Derseh, Behailu Tariku; Wubetu, Abate Dargie; Engidaw, Nigus Alemnew; Gizachew, Kefyalew Dagne
Abstract : Background . Globally, millions of people are affected by human immunodeficiency virus (HIV). Acquired immunodeficiency was linked with psychosocial problems, whereby stigma and discrimination are the most common. Therefore, this study was aimed at assessing the level of the social support problem in people living with human immunodeficiency virus (PLHIV) and factors associated with it at selected hospitals of North Shewa Zone, Amhara Region, Ethiopia. Method . An institution-based cross-sectional study design was employed. A total of 422 PLHIV were involved in the study. A multidimensional perceived social support scale (MPSSS) for the measurement of social support problems was implemented. Systematic random sampling was used to recruit the study population after selecting study areas by lottery methods. Multivariate logistic regression analyses were performed via SPSS software. The statistical association was declared at a p value of less than 0.05 in the final model. Result . The prevalence of poor social support among study participants was 12.6%. Poor adherence to their antiretrovirus drugs was highly associated with poor social support (AOR = 2.06, 95% CI: 1.36, 3.13). Moreover, psychological distress (AOR = 4.67, 95% CI: 2.02, 10.81) and perceived stigma (AOR = 1.78, 95% CI: 1.18, 2.70) were positively associated. Conclusion . The burden of poor social support is increasingly affecting the lives of PLHIV. Poor social support in PLHIV is more magnified by poor adherence, having psychological distress, and perceived stigma.